Analisis Pragmatik Ujaran Kontroversial Ndasmu dalam Wacana Politik Indonesia: Studi Kasus Pidato Presiden Prabowo - Tiwi Widya Lestari; Amelia Amanda Verawati; Adila Nisa Hamidah; Yuwafa Faurelio Yahya; Wawan Hermawan (STIKes Ibnu Sina Ajibarang, 2025)
The phenomenon of social media talk about the ndasmu utterance raises the question of why it has become controversial. Through the pragmatics perspective, this study tries to analyze the speech using a qualitative approach. By collecting data through transcriptions of speeches uploaded on YouTube channels, the data analysis will identify the context, types of speech acts, and the politeness of the word ndasmu in the president's speech. In addition, it is supported by secondary data in the form of public responses in interpreting the speech. The analysis is based on Halliday's situational context theory and Searle's speech acts. The data findings show that the president's speech is an illocutionary speech act with an expressive-satirical form.